Antiviral therapy of hepatitis C with 1 genotype after liver transplantation - O. M. Tsiroulnikova; D. V. Umrik (Вестник трансплантологии и искусственных органов, 2018)
Chronic HCV infection is the leading cause of liver transplantation in adults in developed countries. Unfortunately, the reinfection of the graft inevitably occurs in  all patients with persistent replication of the virus. Against the background of the  necessary immunosuppressive therapy, the progression of the disease accelerates,  leading to rapid decompensation of the liver. Antiviral therapy significantly improves  the results of transplantation, but the use of standard interferon-based  regimens is associated with low efficacy (no more than 30% for the most common 1  genotype of the virus) and poor tolerance. The article describes new interferon- free oral regimens used to treat the recurrence of HCV infection of 1 genotype.